Herbal medicines and thfe use of Glycine Max in climacteric - Ferreira, Lana Hanna Araújo (2021)
Glycine Max is a herbal medicine because a plant is used for the treatment or prevention of diseases, in this case, Glycine Max is a soy derivative that has pharmacological effects thus alleviating various diseases and symptoms, among them the highlights are climacteric effects. To analyze the decrease in climacteric symptoms, this causes discomfort and interferes with the quality of life of women with the use of Glycine max, thus reporting its benefits. This is an integrative literature review, and with regard to the material used, the following research platforms were chosen: Academic Google, Lilacs - Bireme (Latin American and Caribbean Literature in Health Sciences) , NCBI/PubMed (National Center for BiotechnologyInformation) and SciELO (Scientific Electronic Lirary Online). With regard to the methods of inclusion and exclusion, articles available in full, in Portuguese, English or Spanish, published between 2014 and 2020 with thematic relevance, are highlighted, excluding incomplete articles published before 2014. After applying the inclusion and exclusion criteria, 15 articles were selected to be analyzed in this integrative review article. During the analysis of the articles it was noticed that herbal medicines present positive results to the effects of the climacteric, this because the index of active principles is lower and causes a similar impact to medicines with more compound dosage, it was also highlighted that the isoflavones present in soy they are mainly responsible for the balancing effect on women's hormone levels and it is precisely because of this balance that there is a benefit to women from climacteric symptoms. The changes caused by climacteric affect the female body both in its physical and psychological aspects, because hormonal decompensation significantly impacts women, Gleycine Max is responsible for a light and natural hormonal recomposition that positively impacts the woman, despite not being a permanent solution, it was noticed throughout the analyzed studies that the symptoms tend to be controlled with the use of the medication.